Simultaneous adsorption of a mixture of paraquat and dye by NaY zeolite covered with alkylsilane - Nur, Hadi; Manan, Amir Faizal Naidu Abdul; Wei, Lim Kheng; Muhid, Mohd Nazlan Mohd; Hamdan, Halimaton (Elsevier Science B.V., Amsterdam, 2005)

(untitled)
The surfaces of NaY zeolite particles were modified by the alkylsilylation of n-octadecyltrichlorosilane (OTS). Two kinds of modified NaY zeolites were prepared; one with its external surface partially and the other fully covered with alkylsilyl groups. Since the size of OTS is bigger than the pore diameter of NaY, it is attached on the external surface, leaving the internal pore accessible to adsorbate molecules. As a result of alkylsilylation, the adsorption properties of these sorbents were improved. The adsorption properties of these materials were tested by their reaction in a mixture of paraquat and blue dye. The results demonstrate that the alkysilylated NaY materials are capable of simultaneous adsorption of paraquat and blue dye. Paraquat was selectively adsorbed into the internal pore of the zeolite whereas the dye on the externally attached alkylsilyl groups of the sorbent; displaying the unique bimodal amphiphilic character of the alkylsilylated NaY zeolites.